Revolutionizing E-Commerce: Tiktok Shop and Power of Integrated Marketing Communication - Berewot, Juliana; Ariyani, Nafiah (CV ODIS, 2024)
This study investigated how consumer perceptions, integrated marketing communication (IMC), and the whole e-commerce landscape were affected by TikTok Shop's relaunch. Customers were drawn to the platform's apparent novelty as a result of the relaunch's increased curiosity. Customer preferences changed as a result of improved features that increased confidence in TikTok Shop's dependability. IMC was essential in deliberately boosting brand awareness using a variety of platforms, including influencer marketing and short-form films. This promoted a captivating customer experience and raised awareness and comprehension of the relaunch. Significant investment beyond TikTok Shop demonstrated dedication to e-commerce innovation, resulting in increased competition and industry-wide improvements. The strategic investment made by TikTok served as a catalyst, encouraging collaborations and platform innovation that could change the dynamics of e-commerce. TikTok's dedication, in short, launched the e-commerce industry as a whole into an exciting new era of opportunities.